An Analysis of the Changes in Communication Techniques in the Italian Codes of Medical Deontology - Conti, Andrea Alberto (Acta Biomedica Atenei Parmensis, 2017)
Background and Aim of the Work: The code of deontology of the Italian National Federation of the Colleges of Physicians, Surgeons and Dentists (FNOMCeO) contains the principles and rules to which the professional medical practitioner must adhere. This work identifies and analyzes the medical-linguistic choices and the expressive techniques present in the different editions of the code, and evaluates their purpose and function, focusing on the first appearance and the subsequent frequency of key terms. Methods: Various aspects of the formal and expressive revisions of the eight editions of the Codes of Medical Deontology published after the Second World War (from 1947/48 to 2014) are here presented, starting from a brief comparison with the first edition of 1903. Formal characteristics, choices of medical terminology and the introduction of new concepts and communicative attitudes are here identified and evaluated. Results: This paper, in presenting a quantitative and epistemological analysis of variations, modifications and confirmations in the different editions of the Italian code of medical deontology over the last century, enucleates and demonstrates the dynamic paradigm of changing attitudes in the medical profession. Conclusions: This analysis shows the evolution in medical-scientific communication as embodied in the Italian code of medical deontology. This code, in its adoption, changes and adaptations, as evidenced in its successive editions, bears witness to the expressions and attitudes pertinent to and characteristic of the deontological stance of the medical profession during the twentieth century.